2019
DOI: 10.7287/peerj.preprints.27406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The phylogenetic origin and evolution of acellular bone in teleost fishes: insights into osteocyte function in bone metabolism

Abstract: Vertebrate bone is composed of three main cell types: osteoblasts, osteoclasts and osteocytes, the latter being by far the most numerous. Osteocytes are thought to play a fundamental role in bone physiology and homeostasis, however they are entirely absent in most extant species of teleosts, a group that comprises the vast majority of bony ‘fishes’, and approximately half of vertebrates. Understanding how this acellular (anosteocytic) bone appeared and was maintained in such an important vertebrate group has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 98 publications
(237 reference statements)
0
14
0
Order By: Relevance
“…A recent evolutionary analysis suggested that aspidin was the ancestral bone type, with cellular bone evolving from it at least two times in vertebrate evolution (Keating et al 2018). Cellular bone first evolved in osteostracans, and its presence in placoderms, acanthodians, and osteichthyans suggests that cellular bone is a synapomorphy of gnathostomes and osteostracans (Brazeau and Friedman 2014; Davesne et al 2019). Because a healing mechanism is found in both aspidin and cellular bone, and cellular bone evolved from aspidin, it is most parsimonious that the healing mechanism evolved in early vertebrate bone (regardless of its cellularity).…”
Section: Resultsmentioning
confidence: 99%
“…A recent evolutionary analysis suggested that aspidin was the ancestral bone type, with cellular bone evolving from it at least two times in vertebrate evolution (Keating et al 2018). Cellular bone first evolved in osteostracans, and its presence in placoderms, acanthodians, and osteichthyans suggests that cellular bone is a synapomorphy of gnathostomes and osteostracans (Brazeau and Friedman 2014; Davesne et al 2019). Because a healing mechanism is found in both aspidin and cellular bone, and cellular bone evolved from aspidin, it is most parsimonious that the healing mechanism evolved in early vertebrate bone (regardless of its cellularity).…”
Section: Resultsmentioning
confidence: 99%
“…The clade Euteleostei includes approximately two-thirds of teleost diversity (Nelson et al, 2016), yet is only represented by salmoniforms in the sample. This is because euteleosts evolved 'acellular' (or anosteocytic) bone that is entirely devoid of osteocytes (Kölliker, 1859;Moss, 1961;Parenti, 1986;Meunier, 1989;Shahar & Dean, 2013;Davesne et al, 2018Davesne et al, , 2019. Salmoniforms are one of the few exceptions, and may have re-acquired osteocytes secondarily during their early evolution (Davesne et al, 2019).…”
Section: Specimen Samplementioning
confidence: 99%
“…Characterising the variation in osteocyte morphology is fundamental to constraining hypotheses about its biological causes, and can therefore provide insights into the multiple functions of osteocytes in living bone, currently not entirely understood in ray-finned fishes (Shahar & Dean, 2013;Doherty et al, 2015;Currey et al, 2017;Davesne et al, 2019). There are many accounts of variation in osteocyte morphology at different scales within various vertebrate lineages: (1) within a single bone (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, all advanced teleosts lack osteocytes even as adults. Thus, it has been suggested that alternative, osteocyte‐independent, mechanisms of bone regulation exist (Davesne et al ., 2019; Ofer et al ., 2019; Witten & Hall, 2015; Witten & Huysseune, 2009).…”
Section: Introductionmentioning
confidence: 99%